Cui tributum, tributu: Brazilian constitutional religious immunity tax between protection, isonomy and abuse (Research, Society and Development, 2021)
The article analyzes the tax immunity applied to religious entities and their limits. The constitutional principles of religious freedom and secularism are the guaranteeing and protective axes of the legal institute of tax immunity of churches, embodied in art. 150, VI, b and § 4 CF / 88. However, the same instrument of respect and collaboration can also undermine the principle of equality and open space for abuse, deviation and crime. In this context, the research makes a historical reflection on the relationship between religion and the duty to tax, the evolution of Brazilian constitutionalism regarding religious immunity, its scope and limits. Hence the question arises: in what sense can religious tax immunity be a source of protection of fundamental rights and, at the same time, violate the principle of isonomy, and facilitate diverse abuses? The methodology is bibliographic and documentary, of an explanatory, qualitative and theoretical nature. The results obtained lead to the conclusion that the tax waiver of the State through religious tax immunity can present itself in a paradoxical way, between the protection of religious freedom and the promotion of abuses for the malpractice of the specific purposes of the churches.